Respuesta :

Answer:

x=0,x=-4

Step-by-step explanation:

(x+6)(x+6) =8x+36

x^2+12X+36-8X-36=0

X^2+4X=0

x(X+4)=0

You will get x=0 ,x=-4

Answer: x1=-4,x2=0

Step-by-step explanation:

x+6^2=8x+36

Expand the expression

x^2+12x+36=8x+36

Cancel equal terms

x^2+12x=8x

Move the variable to the left

x^2+12x-8x=0

Collect like terms

x^2+4x=0

Factor the expression

x x (x+4) = 0

Separate into possible cases

x=0

x+4=0

Solve the equation

x=0

x=-4

The equation has 2 solutions

x1=-4,x2=0

ACCESS MORE